Differential Response to NaCl Osmotic Stress in Sequentially Harvested Hydroponic Red and Green Basil and the Role of Calcium - Ciriello, Michele; Formisano, Luigi; Soteriou, Georgios A.; Kyratzis, Angelos; De Pascale, Stefania; Kyriacou, Marios C.; Rouphael, Youssef (Frontiers in Plant Science, 2022)
Basil (Ocimum basilicum L.) is a heterogeneous reservoir of bioactive compounds that provide recognized benefits to human health, rendering it a model aromatic herb. Notwithstanding the application of nutritional stress, such as sodium chloride (NaCl) salinity, which mainly affects the primary metabolism, it also triggers adaptive mechanisms that involve the production of bioactive secondary metabolites. Genotype selection and the exogenous application of calcium chloride (CaCl2) help minimize salinity’s suppressive effects on growth. In the present study, we hypothesize that the ratio of different salt types may induce differential responses in the function of preharvest factors in hydroponic basil culture. In this perspective, the stock nutrient solution (Control) was supplemented with 12.5 mm NaCl + 8.33 mm CaCl2 (Moderate Mix), 25 mm NaCl (Moderate NaCl), 25 mm NaCl + 16.66 of CaCl2 (High Mix), or 50 mM of NaCl (High NaCl) with the objective of evaluating the different impact of salinity on yield, sensory quality (color and aroma profile), and the accumulation of minerals and bioactive compounds in two successive harvests of green and red basil cultivars. Although more productive (+39.0% fresh weight) than the red one, the green cultivar exhibited higher susceptibility to salinity, especially under the High Mix and High NaCl treatments. The addition of CaCl2 to the High Mix solution reduced the sodium by 70.4% and increased the total polyphenols by 21.5% compared to the equivalent isomolar solution (High NaCl). The crop performance in terms of fresh and dry yield improved for both cultivars at the second cut. Regardless of cultivar and salt treatment, successive harvests also increased the concentration of phenols and vitamin C (29.7 and 61.5%, respectively) while reducing (−6.9%) eucalyptol, the most abundant aromatic compound in both cultivars. Salinity, as well as the mechanical stress induced by cutting, improved the functional quality of basil. However, the productive responses to the conditions imposed in our work once again highlighted the importance of genetic background. Specifically, CaCl2 in the Moderate Mix solution preserved fresh leaf weight in the most stress-sensitive green cultivar.